PENGARUH MOTIVASI, KOMUNIKASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN DI PIZZA MARZANO CABANG JAKARTA SELATAN - Etty Nurwati; Nur Rahmi (LPPM Universitas Asa Indonesia, 2018)
Purpose- The study aims to determine the independent variable motivation, communication, and discipline to dependent of employee performance in Pizza Marzano branch of South Jakarta. Design/methodology/approach- The study was conducted by using quantitative descriptive technique. The population in this study are employees of Pizza Marzano of South Jakarta as much as 120 employee with a sample of 100 using the slovin formula. The sample used accidental sampling technique. The test results were analyzed with multiple linear regression method using SPSS Statistics 22. The analyzed tecnique used includes of test the validaty and reliability, the classics assumption test in the form of normality test, multicollinearity,heteroscedasticity test, multiple linear regression analysis and hypothesis testingin. Findings- test f, t-test, correlation (R) and the coefficient of determination (R2) and the analysis can seen be the influence of motivation, communication, and discpline has an effect on employee performance partially and simultaneously.